Discrimination of Mangrove Ecosystem Objects on the Visible Spectrum Using Spectroradiometer HR-1024 - Arfan, Amal (Forum Geografi, 2015)
The study was conducted to determine whether the vegetation in the mangrove ecosystem, can be contrasted with another objectt, using Spectroradiometer HR-1024. The data used is data visible spectrum(400-700 nm)Â  which resulted in 204 bands. The analysis used is the integrated analysis with three levels. First, using ANOVA to determine significant differences in spectral reflectance between vegetation with water, wet soil and dry soil. Second, using Step wise Canonical Discriminant Analysis to identify the most sensitive band for discrimination reflection spectrum. This analysis which resulted in six bands are considered practical to distinguish vegetation with another object namelyÂ  401.5 nm, 416.9 nm, 508.2 nm, 599.3 nm, 660.3nm and 689.2 nm. Third using the Jeffries-Matusita separability index which resulted in the separation index of mangrove vegetation, water, wet soil and dry soil is 1.414.